Neural substrates of cognitive impairment in a NMDAR hypofunction mouse model of schizophrenia and partial rescue by risperidone - Delgado-Sallent, Cristina; Gener, Thomas; Nebot, Pau; López-Cabezón, Cristina; Puig, M. Victoria (Frontiers in Cellular Neuroscience, 2023)
N-methyl D-aspartate receptor (NMDAR) hypofunction is a pathophysiological mechanism relevant for schizophrenia. Acute administration of the NMDAR antagonist phencyclidine (PCP) induces psychosis in patients and animals while subchronic PCP (sPCP) produces cognitive dysfunction for weeks. We investigated the neural correlates of memory and auditory impairments in mice treated with sPCP and the rescuing abilities of the atypical antipsychotic drug risperidone administered daily for two weeks. We recorded neural activities in the medial prefrontal cortex (mPFC) and the dorsal hippocampus (dHPC) during memory acquisition, short-term, and long-term memory in the novel object recognition test and during auditory processing and mismatch negativity (MMN) and examined the effects of sPCP and sPCP followed by risperidone. We found that the information about the familiar object and its short-term storage were associated with mPFC→dHPC high gamma connectivity (phase slope index) whereas long-term memory retrieval depended on dHPC→mPFC theta connectivity. sPCP impaired short-term and long-term memories, which were associated with increased theta power in the mPFC, decreased gamma power and theta-gamma coupling in the dHPC, and disrupted mPFC-dHPC connectivity. Risperidone rescued the memory deficits and partly restored hippocampal desynchronization but did not ameliorate mPFC and circuit connectivity alterations. sPCP also impaired auditory processing and its neural correlates (evoked potentials and MMN) in the mPFC, which were also partly rescued by risperidone. Our study suggests that the mPFC and the dHPC disconnect during NMDAR hypofunction, possibly underlying cognitive impairment in schizophrenia, and that risperidone targets this circuit to ameliorate cognitive abilities in patients.